“MENJAGA MARWAH” INSENTIF PERPAJAKAN YANG BERDAMPAK PADA PENERIMAAN PAJAK DI INDONESIA TAHUN 2019 - NOOR SAFRINA; Akhmad Soehartono; Aura Asrina Savitri (JURNAL RISET TERAPAN AKUNTANSI, 2020)
Tax is one of the reliable state revenues. To optimize tax revenue as a source of state revenue, there needs to be excellent service for each taxpayer. The shadows of the lack of tax revenue continue to lurk. Tax revenue performance, which is the biggest contributor to state revenue, began to slow down. This paper wants to reveal whether the various forms of tax incentives are indeed an urgent need for investors? The provision of tax incentives will indeed suppress the performance of tax revenue. Tax incentives are a determinant of investment activities, but not the only one. Do not let the core of the problem be in another domain, but tax incentives are used as a solution. The results of this paper are in the form of an analysis of literature studies that in a broad perspective, temporary tax incentives have a greater short-term impact than permanent policies. Tax incentives are a necessary requirement to spur investment but are not sufficient to reach sustainable economic growth. In essence, the government must